The molecular biology of memory: cAMP, PKA, CRE, CREB-1, CREB-2, and CPEB - Kandel Eric R (Molecular Brain, 2012)
Abstract The analysis of the contributions to synaptic plasticity and memory of cAMP, PKA, CRE, CREB-1, CREB-2, and CPEB has recruited the efforts of many laboratories all over the world. These are six key steps in the molecular biological delineation of short-term memory and its conversion to long-term memory for both implicit (procedural) and explicit (declarative) memory. I here first trace the background for the clinical and behavioral studies of implicit memory that made a molecular biology of memory storage possible, and then detail the discovery and early history of these six molecular steps and their roles in explicit memory.